Electronystagmographic analysis of peripheral vertigo - Suresh, Abinayaah; Narendran, Gitanjali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Examination of the vestibulo-ocular reflex is still the investigation of choice for evaluating the vestibular function to rule out peripheral causes. Aim and objectives were to compare the electronystagmographic changes of all peripheral forms of vertigo and to highlight its significance in the diagnosis and management of the same. Methods: This is a prospective study done after obtaining ethical committee approval in a total of 100 patients attending the ENT OPD at Sri Muthukumaran Medical College Hospital & Research Institute with chief complaints of vertigo. Patients diagnosed with chronic suppurative otitis media, hypertensive patients, h/o seizures, recent cardiac illness or patients on cardiac investigations, psychotic disorders, documented CNS lesions, cervical spondylitis, h/o recent eye/ ear surgery are excluded from this study. ENG analysis includes occulomotor testing, positional testing and caloric stimulation. Evaluation of gait and balance is done followed by maneuver induced vertigo testing (dix hallpike and fistula test) along with PTA. Statistical analysis was done using independent sample t test and chi square test to check the hypothesis using statistical package for social studies SPSS version 17. Results: The observations of ENG like spontaneous nystagmus and bi-thermal caloric test responses are represented on a claussens butterfly chart and the corresponding bar codes were obtained. The inferences for different forms of vertigo were studied. Conclusions: ENG is now an accepted routine and basic investigation in the management of all patients suffering from equilibrium disorders. Management consists of diagnosing the underlying pathology and treatment of the same.